If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9(x + 4) = 81 Reorder the terms: -9(4 + x) = 81 (4 * -9 + x * -9) = 81 (-36 + -9x) = 81 Solving -36 + -9x = 81 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '36' to each side of the equation. -36 + 36 + -9x = 81 + 36 Combine like terms: -36 + 36 = 0 0 + -9x = 81 + 36 -9x = 81 + 36 Combine like terms: 81 + 36 = 117 -9x = 117 Divide each side by '-9'. x = -13 Simplifying x = -13
| 2(2x+11)=3x+8 | | 4/9=5/n-5 | | -6n+21=12-15n | | 4i=8x | | 4i=4x | | 5x=-5-10 | | 0.12(y-7)+0.02y=0.18y-0.9 | | 0.31(2x-1)=-4.3x+2 | | 8(w-3)=-7w-9 | | 3(2n+1.2)=6(3n-2.8) | | 4(ax+3)-ax=25+3a | | (2x-2)+(x+1)-x-(x+1)=60 | | Y=2x^2+13x-24 | | x^(1/3)=-0.5 | | 2x+y+15x-y=3 | | 1.1=3y+11.6 | | 3x-1.5=2(3x+6) | | 7x+3x^2= | | 3x+2(3x+5)= | | 1.8=0.7u+0.1u | | a=3a-36 | | 3-3x=4x-4x | | 4n+3=3 | | 4t-41=3t-20 | | (x)(5/4)/2=100 | | 8u-52=3u-2 | | (x)(5/4)/2=10 | | 2s+50=5s-13 | | 3x/11-9/11=-3/11 | | -20=-8x+5(x-7) | | -5/6x15 | | 2x-1=-2x+31 |